Joining Processes for Fibre-Reinforced Thermoplastics: Phenomena and Characterisation - Troschitz, Juliane; Gröger, Benjamin; Würfel, Veit; Kupfer, Robert; Gude, Maik (Materials)
Thermoplastic composites (TPCs) are predestined for use in lightweight structures, especially for high-volume applications. In many cases, joining is a key factor for the successful application of TPCs in multi-material systems. Many joining processes for this material group are based on warm forming the joining zone. This results in a change of the local material structure characterised by modified fibre paths, as well as varying fibre contents, which significantly influences the load-bearing behaviour. During the forming process, many different phenomena occur simultaneously at different scales. In this paper, the deformation modes and flow mechanisms of TPCs during forming described in the literature are first analysed. Based on this, three different joining processes are investigated: embedding of inserts, moulding of contour joints, and hotclinching. In order to identify the phenomena occurring in each process and to describe the characteristic resulting material structure in the joining zones, micrographs as well as computed tomography (CT) analyses are performed for both individual process stages and final joining zones.

Über die Abgrenzung von Auflösungskonzepten in der industriellen Computertomografie - Binder, Felix; Hausotte, Tino (tm - Technisches Messen)
Unter dem Begriff der Auflösung wird für gewöhnlich das kleinste messbare Merkmal eines Messsystems verstanden. In der dimensionellen Computertomografie hingegen haben sich in den vergangenen Jahren mehrere Auflösungskonzepte etabliert, die aufgrund der fehlenden Normung zueinander im Kontrast stehen. In diesem Beitrag werden die drei häufigsten Konzepte, die Voxelgröße, die Ortsauflösung und die metrologische Strukturauflösung in Kürze vorgestellt. Anschließend wird eine Abgrenzung zwischen den Konzepten getroffen und ein Integration der bestehenden Konzepte in ein gemeinsames Amplituden-Wellenlängen Diagramm diskutiert.
Keywords: Electrical and Electronic Engineering; Instrumentation

Herausforderungen bei computertomografischen Untersuchungen von Fügeverbindungen - Busch, Matthias; Butzhammer, Lorenz; Hausotte, Tino (tm - Technisches Messen)
Die Erkennbarkeit von Rissen und geometrischen Qualitätskennwerten von Fügeverbindungen mittels Computertomografie ist von der Interfacestrukturauflösung abhängig, welche mittels geeigneter Prüfkörper untersucht wird. Die Reduktion von Abbildungsartefakten im Bereich von Bauteilzwischenräumen und -oberflächen verbessert deren dimensionelle Erfassbarkeit.
Keywords: Electrical and Electronic Engineering; Instrumentation

‘Just a Normal Day in the Metaverse’ – Distraction Conflicts of Knowledge Work in Virtual Environments - Marx, Julian; Rieskamp, Jonas; Mirbabaie, Milad (Proceedings of the 33rd Australasian Conference on Information Systems)

Enhanced process development by simulation of ultrasonic heavy wire bonding - Schemmel, Reinhard
Das Ultraschall-Dickdrahtbonden mit Aluminiumdraht ist ein Standardverfahren zur elektrischenKontaktierung von Leistungshalbleitermodulen. Die steigenden Anforderungen an die Effizienzund Zuverlässigkeit der Module haben zu technologischen Weiterentwicklungen geführt und eswerden vermehrt Kupferdrähte mit wesentlich besseren elektrischen und thermischen Eigenschafteneingesetzt. Hieraus resultieren durch höhere Prozesskräfte und Ultraschallleistung neueHerausforderungen bei der Prozessentwicklung; hierfür wird ein Simulationsmodell zur Verbesserungder Prozessentwicklung entwickelt.In Ultraschall-Drahtbondversuchen mit 400 m Aluminium und Kupfer Drähten wurde der Einflussder Prozessparameter auf die Bondqualität untersucht; diese Ergebnisse und zusätzliche Messungender Drahtdeformation und Schwingungen wurden für die Formulierung der Anforderungenund zur Validierung der Ergebnisse des Simulationsmodells genutzt.Es wurde ein Prozessmodell, basierend auf einer Co-Simulation zwischen MATLAB und ANSYS,entwickelt; hierbei wurden die phyiskalischen Phänomene wie die Ultraschall Werkstoffentfestigung,der Verbindungsaufbau und die dynamischen Systemeigenschaften abgebildet.Basierend auf einer Zug-Druck-Prüfmaschine wurde ein Prüfstand zur Identifikation der Modellparameterentwickelt. In zusätzlichen Druckversuchen mit den Bonddrähten mit und ohneUltraschallanregung wurde die Reduktion der Umformkräfte unter Ultraschalleinfluss untersucht.Mit dem entwickelten Prozessmodell wurden die Parameterstudien aus den Ultraschall-Drahtbondversuchensimuliert und direkt mit den experimentellen Ergebnissen verglichen, wobei sich einerelativ gute Übereinstimmung zwischen Simulation und Messung sowohl für Aluminium, als auchfür Kupfer, erzielen ließ.

Potenziale und Grenzen von Unterstützungsmaßnahmen zum wissenschaftlichen Schreiben im Paderborner Physik Praktikum 3P - Bauer, Anna Brigitte; Lahme, Simon Zacharias; Sacher, Marc (PhyDid A - Physik und Didaktik in Schule und Hochschule)
Eines der Lernziele des Physikstudiums stellt der Erwerb literaler Fähigkeiten für das Verfassen wissenschaftlicher Arbeiten dar. Die Student:innen werden allerdings im Rahmen ihres Studiums bisher kaum systematisch beim Erwerb dieser Fähigkeiten unterstützt. Eine Übungsgelegenheit für das Verfassen von Texten nach wissenschaftlichem Vorbild stellt das Laborpraktikum dar, in dem die Student:innen zu den absolvierten Experimenten Laborberichte verfassen. Im Paderborner Physik Praktikum 3P wurden in den letzten Jahren vier unterschiedliche Unterstützungsangebote für das Erlernen des wissenschaftlichen Schreibens entwickelt und mittels Zufriedenheitswerten evaluiert. In dem Beitrag werden die vier Angebote auf inhaltlicher Ebene hinsichtlich der Lernwirksamkeit mittels einer schriftproduktbasierten Evaluation analysiert. Durch die vergleichende Analyse können Potenziale und Grenzen der Angebote diskutiert und Implikationen für die Gestaltung von Unterstützungsangeboten zum Erlernen des wissenschaftlichen Schreibens in der Physik abgeleitet werden.
Keywords: Laborpraktikum; Schreiben

Time-resolved terahertz–Raman spectroscopy reveals that cations and anions distinctly modify intermolecular interactions of water - Balos, Vasileios; Kaliannan, Naveen Kumar; Elgabarty, Hossam; Wolf, Martin; Kühne, Thomas; Sajadi, Mohsen (Nature Chemistry)
Abstract The solvation of ions changes the physical, chemical and thermodynamic properties of water, and the microscopic origin of this behaviour is believed to be ion-induced perturbation of water’s hydrogen-bonding network. Here we provide microscopic insights into this process by monitoring the dissipation of energy in salt solutions using time-resolved terahertz–Raman spectroscopy. We resonantly drive the low-frequency rotational dynamics of water molecules using intense terahertz pulses and probe the Raman response of their intermolecular translational motions. We find that the intermolecular rotational-to-translational energy transfer is enhanced by highly charged cations and is drastically reduced by highly charged anions, scaling with the ion surface charge density and ion concentration. Our molecular dynamics simulations reveal that the water–water hydrogen-bond strength between the first and second solvation shells of cations increases, while it decreases around anions. The opposite effects of cations and anions on the intermolecular interactions of water resemble the effects of ions on the stabilization and denaturation of proteins.
Keywords: General Chemical Engineering; General Chemistry

Systems Engineering - verstehen und industriell umsetzen - Gräßler, Iris; Oleff, Christian
Wie werden technische Systeme zeitgemäß entwickelt, die in Komplexität und Anspruch alles bisher Dagewesene übertreffen? Darauf gibt Systems Engineering Antworten. Bisherige Beschreibungen sind für den Maschinenbau aber oft schwer greifbar und zu unkonkret. Dieses Buch bricht den internationalen Stand der Wissenschaft auf das Wesentliche herunter und beschreibt praxisnah die Kernelemente des Systems Engineering. Eine konkrete Schritt-für-Schritt Anleitung ebnet den Weg für den erfolgreichen Transfer aus der klassischen Produktentwicklung hin zum Systems Engineering. Die Inhalte werden grafisch professionell und bewusst lebendig vermittelt. So wird nicht nur ein fundiertes Systems Engineering-Verständnis geschaffen, sondern auch die Basis für Kommunikation und Umsetzung im Unternehmen gelegt.

Knowledge and Data-Based Design and Dimensioning of Mechanical Joining Connections - Zirngibl, Christoph; Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro (Volume 2: 42nd Computers and Information in Engineering Conference (CIE))
Challenges in the development of resource-efficient lightweight designs, such as emission and cost targets in production, lead to an increasing demand for environmentally friendly and fast joining processes. Therefore, cold-forming mechanical joining techniques provide an energy-efficient alternative in comparison to established processes, such as spot welding. However, to ensure a sufficient reliability of the product design, not only the selection of an appropriate manufacturing and joining method, but also the suitable dimensioning and validation of the entire joining process is a crucial step. In this context, thermal processes offer a large number of design principles while mechanical joining methods mainly require extensive experimental tests and the inclusion of expert knowledge. Although few contributions already investigated the data-based analysis of mechanical joints, a system for the requirement- and manufacturing-oriented dimensioning of joining components, such as different profiles and blanks, in combination with the estimation of joint properties is not available yet. Motivated by this lack, this contribution introduces an engineering workbench for the support of design engineers in the early development phases of the knowledge and data-based design of mechanical joining connections using clinching as an example. In this regard, the approach is demonstrated involving a similar material and sheet thickness combination with static loads.

Estimation of Clinch Joint Characteristics Based on Limited Input Data Using Pre-Trained Metamodels - Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (AI)
Given strict emission targets and legal requirements, especially in the automotive industry, environmentally friendly and simultaneously versatile applicable production technologies are gaining importance. In this regard, the use of mechanical joining processes, such as clinching, enable assembly sheet metals to achieve strength properties similar to those of established thermal joining technologies. However, to guarantee a high reliability of the generated joint connection, the selection of a best-fitting joining technology as well as the meaningful description of individual joint properties is essential. In the context of clinching, few contributions have to date investigated the metamodel-based estimation and optimization of joint characteristics, such as neck or interlock thickness, by applying machine learning and genetic algorithms. Therefore, several regression models have been trained on varying databases and amounts of input parameters. However, if product engineers can only provide limited data for a new joining task, such as incomplete information on applied joining tool dimensions, previously trained metamodels often reach their limits. This often results in a significant loss of prediction quality and leads to increasing uncertainties and inaccuracies within the metamodel-based design of a clinch joint connection. Motivated by this, the presented contribution investigates different machine learning algorithms regarding their ability to achieve a satisfying estimation accuracy on limited input data applying a statistically based feature selection method. Through this, it is possible to identify which regression models are suitable to predict clinch joint characteristics considering only a minimum set of required input features. Thus, in addition to the opportunity to decrease the training effort as well as the model complexity, the subsequent formulation of design equations can pave the way to a more versatile application and reuse of pretrained metamodels on varying tool configurations for a given clinch joining task.
Keywords: Industrial and Manufacturing Engineering

Das Leben nehmen oder den Tod geben – Selbstbestimmtes Sterben auf der Schwelle von Utopie zur Realität? - Harmening, Anda-Lisa Martha Josephine Anna (Sonderausgabe des Jahrbuchs für internationale Germanistik 2022)

Wissenstransfer als Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung

Twenty-First Century Anxieties: Dys/Utopian Spaces and Contexts in Contemporary British Theatre

Directing Pandemic Attention: Dystopian Corona Narratives and the Nation in British Media and Politics - Tönnies, Merle; Flotmann-Scholz, Christina (Anglistik: International Journal of English Studies)

Anger, Anxiety and Hope: The Complicit Realities and Engaged/ing Communities of Contemporary Briitsh Dys/Utopian Theatre - Tönnies, Merle; Voigts, Eckart (Twenty-First Century Anxieties: Dys/Utopian Spaces and Contexts in Contemporary British Theatre (CDE Studies))

Weil wir tatsächlich nicht voneinander wussten, was jeder Einzelne so an verborgenen Schätzen bringt - Lütje-Klose , Birgit; Grüter, Sandra; Neumann, Phillip; Weber, Antonia; Goldan, Janka; Gorges, Julia; Wild, Elke (Qualifizierung für Inklusion. Sekundarstufe)

Design and investigation of a metalens for efficiency enhancement of laser-waveguide coupling in a limited space system - laeim, Huddad; Schlickriede, Christian; Chaisakul, Papichaya; Chattham, Nattaporn; Panitchakan, Hathai; Siangchaew, Krisda; Zentgraf, Thomas; Pattanaporhratana, Apichart (Metamaterials, Metadevices, and Metasystems 2022)

Return to sports after ACL injury 5 years from now: 10 things we must do - Gokeler, Alli; Grassi, Alberto; Hoogeslag, Roy; van Houten, Albert; Bolling, Caroline; Buckthorpe, Matthew; Norte, Grant; Benjaminse, Anne; Heuvelmans, Pieter; Di Paolo, Stefano; Tak, Igor; Villa, Francesco Della (Journal of Experimental Orthopaedics)
Abstract Background The outcome after ACL reconstruction (ACLR) is in general disappointing with unacceptable number of athletes that do not return to pre-injury level of sports, high re-injury rates, early development of osteoarthritis and shorter careers. Athletes after ACLR have high expectation to return to sports which is in contrast with the current outcomes. The aim of this manuscript is to present an overview of factors that are needed to be incorporated and to personalize the rehabilitation process for an athlete who has undergone an ACLR. Level of evidence 4.
Keywords: Orthopedics and Sports Medicine

Cortical responses to sport-specific stimuli in a standing stop signal task - Scharfen, Hans-Erik; Lehmann, Tim; Büchel, Daniel; Baumeister, Jochen (Psychology of Sport and Exercise)
Keywords: Applied Psychology

Comparing lab and field agility kinematics in young talented female football players: Implications for ACL injury prevention - Di Paolo, Stefano; Nijmeijer, Eline; Bragonzoni, Laura; Dingshoff, Evelien; Gokeler, Alli; Benjaminse, Anne (European Journal of Sport Science)
Keywords: Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine